Prenatal Seasonality, Child Growth, and Schooling Investments : Evidence from Rural Indonesia - Yamauchi, Futoshi (Taylor and Francis, 2013)
This article examines the impacts of prenatal conditions on child growth using recent data from Indonesia. There is seasonality in birthweight: this measure is significantly higher immediately after the main rice harvest in the country. The empirical results show that an increase in birthweight improves child growth outcomes as measured by the height and weight z-scores, as well as schooling performance as measured by age at start of schooling and number of grades repeated. The interactions of ecological variations affect early childhood human capital formation and can have long-term impacts on children's outcomes.